2012
DOI: 10.1029/2011ja017103
|View full text |Cite
|
Sign up to set email alerts
|

Quiet time variability of the GPS TEC and EEJ strength over Indian region associated with major sudden stratospheric warming events during 2005/2006

Abstract: [1] This paper describes the quiet time variabilities of the ionospheric total electron content (TEC) derived from the signals from Global Positioning Satellite System (GPS) recorded at several stations in India along with simultaneous observations of equatorial electrojet (EEJ) strength obtained from geomagnetic field variations during January-March 2006 when sudden stratospheric warming (SSW) events occurred. Analysis of the observations presented here confirms that strong correlation exists among the variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 65 publications
3
41
2
Order By: Relevance
“…Abdu (2006) found that the planetary wave modulating the E region tidal winds leads to planetary-wave-scale oscillations in the plasma vertical drift velocity in the equatorial ionosphere. Recent studies revealed that quasi-16-day periodicity was observed in the equatorial mesopause and lower thermosphere temperature, electron density and TEC in EIA region, and EEJ during the same time period due to the quasi-16-day planetary wave modulating the tidal amplitudes in the ionospheric dynamo region (Vineeth et al, 2007;Pedatella and Forbes, 2009;Sripathi and Bhattacharyya, 2012). Besides the mechanism of the nonlinear interaction of upward propagating 16-day periodic planetary wave with atmospheric tides, the strongly enhanced semidiurnal lunar tide has also been noted and has been considered to explain the quasi-16-day periodic variation observed in EEJ and ionosphere in some SSW case studies (Fejer et al, 2010;Eccles et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdu (2006) found that the planetary wave modulating the E region tidal winds leads to planetary-wave-scale oscillations in the plasma vertical drift velocity in the equatorial ionosphere. Recent studies revealed that quasi-16-day periodicity was observed in the equatorial mesopause and lower thermosphere temperature, electron density and TEC in EIA region, and EEJ during the same time period due to the quasi-16-day planetary wave modulating the tidal amplitudes in the ionospheric dynamo region (Vineeth et al, 2007;Pedatella and Forbes, 2009;Sripathi and Bhattacharyya, 2012). Besides the mechanism of the nonlinear interaction of upward propagating 16-day periodic planetary wave with atmospheric tides, the strongly enhanced semidiurnal lunar tide has also been noted and has been considered to explain the quasi-16-day periodic variation observed in EEJ and ionosphere in some SSW case studies (Fejer et al, 2010;Eccles et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Using the ionospheric electron densities from the CHAllenging Minisatellite Payload (CHAMP) satellite and ionospheric total electron content (TEC) data from GPS during the same period, Pedatella and Forbes (2009) found the quasi-16-day oscillation in these density parameters at low latitude and suggested that vertically propagating planetary waves induce significant variability in the low-latitude F region ionosphere. More recently, using ionospheric TEC from GPS observations in the Indian sector, Sripathi and Bhattacharyya (2012) also studied the ionospheric periodic variability during 2005-2006 SSW event and suggested that this kind of periodic variability in TEC is caused by the nonlinear interaction of upward propagating planetary waves with atmospheric tides. In their study, the quasi-periodic oscillation of the latitude of the EIA crest was revealed qualitatively.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this change in its interaction, the polar stratospheric temperature increases during several days. Recently, an unforeseen coupling between high latitudes, midlatitudes, and equatorial/low latitudes at upper atmospheric/ionospheric altitudes was discovered during sudden stratospheric warming (SSW) events [Goncharenko and Zhang, 2008;Goncharenko et al, 2010aGoncharenko et al, , 2010bGoncharenko et al, , 2013aGoncharenko et al, , 2013bVineeth et al, 2009;Chau et al, 2010Chau et al, , 2012Liu et al, 2011;Pancheva and Mukhtarov, 2011;Bessarab et al, 2012;Fang et al, 2012;Korenkov et al, 2012;Sripathi and Bhattacharyya, 2012;Sumod et al, 2012;Olson et al, 2013;Upadhayaya and Mahajan, 2013;Xiong et al, 2013;Pedatella et al, 2014aPedatella et al, , 2014b. Therefore, various aspects involved behind the effects of SSW need to be explored in order to improve our knowledge about the Earth's atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The parameter EEJ proxy index ( H TIR − H ABG ) is obtained by subtracting the nighttime baseline of magnetometer H variation from the daytime values at equatorial Tirunelveli and off-equatorial Alibag observatory, and then finding the difference between them, ensuring the removal of the core and large-scale magnetospheric fields. This method was initially suggested by Chandra et al (1971) and later used by several workers (Bhargava et al 1983;Rastogi and Klobuchar 1990;Alex and Mukherjee 2001;Jose et al 2011;Sripathi and Bhattacharyya 2012) and many more. The F2-layer parameters at Trivandrum and Delhi are examined in this study to realize the ionospheric behavior over equatorial and beyond EIA crest low latitudes respectively.…”
Section: Data Methods Of Processing and Analysismentioning
confidence: 96%